Evaluasi Kapasitas Agroekosistem dalam Mendukung Populasi Sapi Potong Nasional Berbasis Wilayah: Evaluation of Agroecosystem Carrying Capacity in Supporting the National Cattle Population: A Regional-Based Analysis - Fellyanus Haba Ora (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2026)
This research aimed to evaluate population density and the agroecosystem carrying capacity of cattle in Indonesia during the 2009–2025 period in order to formulate region-based development directions according to regional typology. The research applied a purposive sampling approach and comparative analysis based on island agroecosystem zones, covering Sumatra, Java, Bali–Nusra, Kalimantan, Sulawesi, and Papua–Maluku. Secondary data were analyzed using indicators of population structure and regional capacity, including economic density, regional density, farming business density, Location Quotient (LQ), Livestock Concentration Index (LCI), Feed Concentration Index (FCI), Carrying Capacity and Carrying Capacity Index (CCI) based on digestible dry matter production of forage and agricultural by-product residues. The results showed that national cattle population growth tended to fluctuate and remained predominantly below 5% per year, indicating that it has not fully supported domestic consumption demand nor reduced imports. Spatially, Java Island remains the main population center but is categorized as densely populated and approaching its ecological limit (CCI 1.24), while Sumatra and Sulawesi are classified as base regions experiencing critical carrying capacity pressure (CCI < 1). Bali–Nusra, Kalimantan, and Papua–Maluku demonstrate development potential, although several areas show limitations in actual carrying capacity. Feed resources across all regions are still dominated by agricultural by-product residues, with relatively low contributions from natural forage.